2017
DOI: 10.1002/cepa.343
|View full text |Cite
|
Sign up to set email alerts
|

11.11: Rocking damage‐free steel column base with friction devices: Development of advanced 3D finite element models in Abaqus

Abstract: Column bases are critical components of a seismic-resistant steel building as they transfer gravity and lateral forces to the foundations. This paper focuses on the finite element (FE) modelling of a rocking damage-free steel column base, which uses post-tensioned high strength steel bars to achieve self-centering behavior and friction devices to provide energy dissipation capacity. Contrary to conventional steel column bases, the monotonic and cyclic moment-rotation behavior of the column base can be easily d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For column base friction connections ( Figure 2 [ 17 ]), Borzouie et al [ 17 ] conducted experimental studies on the cyclic performance of column base strong and weak axis aligned asymmetric friction connection, and it was found that the proposed details for base connections with friction connections provide repeatable cycles without strength degradation or any requirements for repair or replacement following an earthquake. Freddi et al [ 18 ] and Dimopoulos et al [ 19 ] also proposed a new type of a sway damage-free steel column base connection and the results of finite element simulation verified the accuracy of the M - θ curve. This kind of connection can effectively avoid yielding of the column base, thus, achieving the objective of damage-free energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…For column base friction connections ( Figure 2 [ 17 ]), Borzouie et al [ 17 ] conducted experimental studies on the cyclic performance of column base strong and weak axis aligned asymmetric friction connection, and it was found that the proposed details for base connections with friction connections provide repeatable cycles without strength degradation or any requirements for repair or replacement following an earthquake. Freddi et al [ 18 ] and Dimopoulos et al [ 19 ] also proposed a new type of a sway damage-free steel column base connection and the results of finite element simulation verified the accuracy of the M - θ curve. This kind of connection can effectively avoid yielding of the column base, thus, achieving the objective of damage-free energy dissipation.…”
Section: Introductionmentioning
confidence: 99%